COCONUT MARKETING: ISSUES FOR A THREATENED INDUSTRY - GEOFFREY BASTIN (International Coconut Community, 1986)
The coconut industry is under pressure from low world oil‑seed prices and the increased availability of palm kernels. This paper reviews market conditions in the lauric sub‑sector, describes the marketing channels for copra and coconut oil, and sets out details of significant issues for the future. It concludes that the industry must take urgent steps to (a) improve the flow of market information, (b) develop cost saving means of production which lead to a range of items, and (c) investigate new markets for non-traditional products.